1997
DOI: 10.1074/jbc.272.9.6004
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Concentration Contributes to Discrimination against Poly(A)− mRNA during Translation Initiation in Saccharomyces cerevisiae

Abstract: Inactivation ofVirtually all known eukaryotic precursor mRNAs undergo processing to mature forms by a series of intranuclear posttranscriptional modifications including intron removal (splicing), 5Ј-end capping, 3Ј-end cleavage and polyadenylation, and in some cases, coding sequence editing. Although normal splicing and editing ensure appropriate coding information, both end modifications have a particular impact on regulating expression levels of mature mRNA. Numerous studies have shown that cap structures se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…The poly(A) tail found at the 39 end of eukaryotic messenger RNAs (mRNAs) is an essential modification that occurs at the posttranscriptional level (for reviews, see Keller, 1995;Manley & Takagaki, 1996;Wahle & Keller, 1996;Colgan & Manley, 1997;)+ Besides its probable involvement in nucleocytoplasmic transport and RNA localization, the poly(A) tail plays important roles in mRNA stability and in translation (Gallie, 1991;Gallie & Tanguay, 1994;Caponigro & Parker, 1995; for reviews, see Sachs & Wahle, 1993;Jacobson & Peltz, 1996;Sachs et al+, 1997)+ The function of the poly(A) tail in translation is mediated by Pab1p (Sachs & Davis, 1989;Tarun & Sachs, 1995)+ Synthetic lethal interaction and coimmunoprecipitation studies showed that the eukaryotic translation initiation factor eIF4G binds Pab1p and that this binding is required to stimulate translation of polyadenylated mRNAs (Tarun & Sachs, 1996;Tarun et al+, 1997)+ Because eIF4G also interacts with the cap-binding protein eIF4E (Haghighat & Sonenberg, 1997), a direct link between the 39 and the 59 ends of the mRNA is likely to occur+ Consistent with these observations, discrimination against poly(A)-deficient mRNAs was observed during translation when synthesis of ribosomal subunits was impaired (Proweller & Butler, 1997)+ Synthetic lethality (Huffacker et al+, 1987;Guarente, 1993) has been shown to be an efficient genetic method in the analysis of multisubunit complexes involved in splicing, rRNA processing, or nucleopore assembly (Frank et al+, 1992;Venema & Tollervey, 1996;Doye & Hurt, 1997)+ In order to find new factors potentially involved in mRNA 39-end formation, we have screened for mutations that confer synthetic lethality with a poly(A) polymerase temperature-sensitive mutant, pap1-7+ We have restricted our analysis to mutations that conferred a temperature-sensitive phenotype because such mutants would likely display a deficient 39-end processing activity on their own+ We have isolated five synthetic lethal, temperature-sensitive lcp mutations (for lethal with conditional pap1 allele)+ Here we report the cloning and characterization of LCP5+ Surprisingly, this mutation impaired the processing of ribosomal RNA precursors, but showed normal pre-mRNA 39-end processing activity+…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…The poly(A) tail found at the 39 end of eukaryotic messenger RNAs (mRNAs) is an essential modification that occurs at the posttranscriptional level (for reviews, see Keller, 1995;Manley & Takagaki, 1996;Wahle & Keller, 1996;Colgan & Manley, 1997;)+ Besides its probable involvement in nucleocytoplasmic transport and RNA localization, the poly(A) tail plays important roles in mRNA stability and in translation (Gallie, 1991;Gallie & Tanguay, 1994;Caponigro & Parker, 1995; for reviews, see Sachs & Wahle, 1993;Jacobson & Peltz, 1996;Sachs et al+, 1997)+ The function of the poly(A) tail in translation is mediated by Pab1p (Sachs & Davis, 1989;Tarun & Sachs, 1995)+ Synthetic lethal interaction and coimmunoprecipitation studies showed that the eukaryotic translation initiation factor eIF4G binds Pab1p and that this binding is required to stimulate translation of polyadenylated mRNAs (Tarun & Sachs, 1996;Tarun et al+, 1997)+ Because eIF4G also interacts with the cap-binding protein eIF4E (Haghighat & Sonenberg, 1997), a direct link between the 39 and the 59 ends of the mRNA is likely to occur+ Consistent with these observations, discrimination against poly(A)-deficient mRNAs was observed during translation when synthesis of ribosomal subunits was impaired (Proweller & Butler, 1997)+ Synthetic lethality (Huffacker et al+, 1987;Guarente, 1993) has been shown to be an efficient genetic method in the analysis of multisubunit complexes involved in splicing, rRNA processing, or nucleopore assembly (Frank et al+, 1992;Venema & Tollervey, 1996;Doye & Hurt, 1997)+ In order to find new factors potentially involved in mRNA 39-end formation, we have screened for mutations that confer synthetic lethality with a poly(A) polymerase temperature-sensitive mutant, pap1-7+ We have restricted our analysis to mutations that conferred a temperature-sensitive phenotype because such mutants would likely display a deficient 39-end processing activity on their own+ We have isolated five synthetic lethal, temperature-sensitive lcp mutations (for lethal with conditional pap1 allele)+ Here we report the cloning and characterization of LCP5+ Surprisingly, this mutation impaired the processing of ribosomal RNA precursors, but showed normal pre-mRNA 39-end processing activity+…”
Section: Introductionsupporting
confidence: 55%
“…Antibodies directed against Lcp5p precipitate U3 snoRNA+ Immunoprecipitation was performed with protein A-tagged fusions of Gar1p (lane 2), Nop1p (lane 3), and with antibodies directed against Lcp5p (lanes 4, 6 and 8) or its cognate preserum (lanes 5, 7 and 9) at the indicated salt concentration (top)+ Lane 10: Mock precipitation without antibody+ Precipitated RNAs were subjected to Northern hybridization with oligonucleotides complementary to snR10, snR17, snR30 and snR128+ FIGURE 9. Synthetic lethality of fal1 and lcp5 mutant alleles+ Strains deleted for both fal1 and lcp5 rescued by the wild-type FAL1 gene and the mutant alleles lcp5-1, fal1-1 or fal1-9 (on centromeric plasmids) were streaked on SC or 5-FOA-containing SC-plates+ Plates were incubated at 24 8C+ ribosomal subunits and hypersensitivity to aminoglycosidic antibiotics (neomycin and paromomycin) and to cycloheximide+ Hypersensitivity to paromomycin has been reported for mutants in NSR1, the putative yeast nucleolin homologue (Lee et al+, 1992) and in FAL1 (Kressler et al+, 1997)+ As a result, both gene products were shown to be involved in 18S rRNA maturation+ Aminoglycosidic antibiotics inhibit early steps in translation (Eustice & Wilhelm, 1984b), act as suppressors of nonsense codons (Palmer et al+, 1979;Singh et al+, 1979) and cause misreading in translation (Eustice & Wilhelm, 1984a)+ Cycloheximide binds to the 60S ribosomal subunit and inhibits both initiation and elongation of translation (Hampsey, 1997)+ The observed hypersensitivity is consistent with a defective translation initiation in lcp5 mutants as a consequence of a reduced amount of 40S ribosomal subunits+ Polysome profile analyses confirmed that translation is impaired in lcp5-1 mutants+ Almost all the ribosomal subunits were present in subpolysomal fractions+ The low number of free 40S ribosomal subunits due to deficient 18S rRNA formation probably prevents efficient polysome formation (see Table 2)+ Therefore, antibiotics that lead to aberrant translation products or inhibit initiation of translation enhance the mutant phenotype beyond a tolerable level+ It is likely that the enhanced turnover of R-Lcp5p in vivo, even when cells were cultured in YPGalactose, led to an increase in free 60S ribosomal subunits and 80S monosomes compared to the wildtype control (compare Fig+ 6A with 6C)+ This is in agreement with Northern-blot analyses of R-Lcp5p expressing cells (compare Fig+ 4A, lanes 1 and 2, to Fig+ 3B, panel C, lane LCP5 )+ The amount of 18S rRNA correlates well with the strength of the observed phenotypes (results not shown)+ Biochemical and genetic analyses have shown that poly(A)-bound Pab1p binds to the initiation factor eIF4G (Tarun & Sachs, 1996;Tarun et al+, 1997) which in turn recognizes the 59 cap structure via the cap binding protein eIF4E (Haghighat & Sonenberg, 1997)+ Recently, it has also been shown that mRNAs with shorter poly(A) tracts are shifted towards monosomes in polysome profiles of mutant pap1-1 cells when ribosomal subunits are depleted at the same time (Proweller & Butler, 1997)+ Similarly, a more severe depletion of the 40S small ribosomal subunit because of pre-rRNA processing defects, as observed in lcp5 mutants, could lead to inefficient translation and eventually to cell death in the lcp5-1 pap1-7 double mutant+ Other experiments also suggested that synthetic lethality between pap1 and...…”
Section: Discussionmentioning
confidence: 99%
“…10, 21, and 66), ribosomal availability as a specific translational determinant has not been extensively investigated. However, genetic evidence from yeast suggests that ribosomal abundance may be of particular importance for translation of nonadenylated mRNAs (67). It is noteworthy that the accumulation of globin mRNAs in differentiating erythrocytes is dependent upon a stability sequence in their 3Ј-untranslated regions, which has been proposed to inhibit deadenylation (68 -70).…”
Section: Discussionmentioning
confidence: 99%
“…2), the so-called "closed loop" configuration of the mRNA resulting from the interaction between poly(A) binding protein (PABP) bound to the 3Ј−poly(A) tail and the eIF4G subunit of the eIF4F complex bound to the 5Ј-end via its eIF4E subunit (Sachs et al 1997;Imataka et al 1998). A closed loop mRNA configuration greatly enhances translation efficiency, particularly under conditions of strong competition between different mRNAs (Proweller and Butler 1997), i.e., a relatively high ratio of mRNA to ribosomes and/or initiation factors.…”
Section: What Are Micrornas and How Do They Differ From Other Small Rmentioning
confidence: 99%